IR 4.0. IN PARLIAMENT: CONCEPTUALISING THE APPLICATION OF ARTIFICIAL INTELLIGENCE AND MACHINE LEARNING IN THE PARLIAMENT OF MALAYSIA’S PARLIAMENTARY QUESTIONS - Muthanna Saari, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The Fourth Industrial Revolution (IR 4.0.) offers significant opportunities to humankind in revitalising human values through which the emerging technologies inevitably seam into daily societal life. Legislatures face ever-increasing challenges in fulfilling their duties in such a complicated society which subsequently entails complex legislations. Parliamentary questions (PQs) as one of the traditional tools utilised by parliamentarians provide a quintessential mechanism to achieve the oversight functions of parliament. However, there are still immense undiscovered potentials of PQs, yet many previous studies have not looked into the content of the questions and the consequences of the response to the conduct of governments. This paper set out to examine the usefulness of IR 4.0. namely, artificial intelligence (AI) and machine learning towards improving the efficiency, transparency, and accountability of parliament and the government. The research data of this exploratory and interpretative study is drawn from three main sources: literature studies, semi-structured interviews, and participant observation of the existing PQs processing in the Dewan Rakyat, Parliament of Malaysia. This study has found that generally, the approval of such technologies introduction to the parliamentary businesses is contingent upon its ability to capture complex considerations in the existing environment.